2008
DOI: 10.1177/0145721708317869
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Psychological Insulin Resistance

Abstract: The results of the surveys, which were generally consistent, identified several remediable misconceptions regarding insulin therapy and suggest targets for educational interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
178
3
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(196 citation statements)
references
References 11 publications
13
178
3
2
Order By: Relevance
“…It has also been found that patients may not be aware of the fact that diabetes may not always be managed with exercise, diet, or oral-antidiabetics Larkin et al, 2008). In this regard, the figures observed in our study were much higher than those previously reported.…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…It has also been found that patients may not be aware of the fact that diabetes may not always be managed with exercise, diet, or oral-antidiabetics Larkin et al, 2008). In this regard, the figures observed in our study were much higher than those previously reported.…”
Section: Discussioncontrasting
confidence: 82%
“…For instance, 44.8% and 61% of the patients were reported to hold these type of beliefs in the studies by Polonsky et Previous reports have suggested that social stigmatization represents an important cause of psychogenic resistance toward initiation of insulin therapy, and patients were reluctant to perform insulin injections when accompanied by others. For instance, in a study involving diabetic patients 25% of the individuals reported that they were embarrassed from insulin injections, and 45% believed that others would consider them as "sick" if they performed injections (Larkin et al, 2008). In our study, 80% of the subjects believed that others would label them as "sick", and 30% reported embarrassment with insulin injections.…”
Section: Discussionmentioning
confidence: 40%
See 3 more Smart Citations